The large and central Caligo martia eyespot may reduce fatal attacks by birds: a case study supports the deflection hypothesis in nature - Iserhard, Cristiano Agra; Malta, Shimene; Penz, Carla; Fraga, Brenda Barbon; Costa, Camila Abel; Schwantz, Taiane; Bordin, Kauane Maiara (Peer Community Journal)

(untitled)
Many animals have colorations that resemble eyes, but the functions of such eyespots are debated. Caligo martia (Godart, 1824) butterflies have large ventral hind wing eyespots, and we aimed to test whether these eyespots act to deflect or to thwart bird attacks through intimidation in a natural community in a Restinga Forest in austral South America. We used four types of paper facsimiles: unmanipulated C. martia (with eyespots, WE), facsimiles with UV enhanced eyespots (UV), camouflaged facsimiles lacking eyespots (CM), and light-coloured facsimiles that were not camouflaged and lacked eyespots (NC). Two experiments were performed: Experiment 1 used facsimiles in a natural resting position, and in Experiment 2 facsimiles were positioned with the wings open, with ventral wing surfaces and body exposed to viewers. In both experiments facsimiles were placed in two forest sites, organized in 50 blocks with four facsimiles each, and checked for predator attacks every 24 h for five consecutive days. While WE and UV facsimiles were mostly attacked in non-vital areas (wings), most bird attacks on CM were directed at vital body areas. Notably, CM facsimiles had lower attack probability than WE, UV and NC. Our results indicate that C. martia eyespots appear to have a deflection function. Eyespots did not appear to reduce attack rates, suggesting that local bird species were not intimidated. Both eyespots and camouflage can be considered efficient functional traits in defence against predation in forest environments, and experiments focusing on local predators and prey are key to our understanding of wing pattern evolution in Lepidoptera.